(untitled) (Oratio Directa, 2018)
The identity of women workers in the formal sector is obtained through social interaction and continuous communication conducted by woman workers at Daar elQolam boarding school.communication contends that self identity as social being is formed in such a way that it becomes a social creature that does not communication interpersonal but also build relationships within it. The method used in this research is phenomenology method with qualitative approach and using constructivist paradigm. This research was conducted at Daar el-Qolam boarding School which employs women as laundry workers who come from the surrounding environment. The result of the study show that the identity of women worker is formed by the process of social interaction,interpersonal communication. Other factor that shape the self identity are selfactualization,self – disclosure and self concept.